2007
DOI: 10.1510/icvts.2006.150664
|View full text |Cite
|
Sign up to set email alerts
|

Factors causing inaccurate staging of mediastinal nodal involvement in non-small cell lung cancer patients staged by positron emission tomography

Abstract: Despite documented superiority of positron emission tomography over other investigative modalities in the preoperative staging of non-small cell lung cancer, a proportion of patients will have an inaccurate staging of their mediastinal nodes. The aim of this retrospective review is to analyse the clinicopathological factors responsible for inaccurate nodal staging by integrated PET-CT. A total of 100 consecutive patients with histologically proven non-small cell lung cancer underwent staging with PET-CT prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…In fact, we had 10.5% of false negative and 8.5% of false positive cases. A high rate of false negative patients for N2 disease in the adenocarcinoma group was identified, as with other authors [35].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In fact, we had 10.5% of false negative and 8.5% of false positive cases. A high rate of false negative patients for N2 disease in the adenocarcinoma group was identified, as with other authors [35].…”
Section: Discussionsupporting
confidence: 83%
“…In conclusion he stressed the necessity to identify the subset of patients with a negative PET/CT, that could benefit from a mediastinoscopy [25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FDG PET can reflect physiologic and biochemical functions and is useful for differential diagnosis of benign and malignant lesions (14)(15)(16). However, there are numerous causes of 18 F-FDG uptake in benign processes, which lead to false-positive results (1,(17)(18)(19) even when PET/CT is also used (20,21). Some investigators have reported that short-t inversion-recovery (STIR) MRI has utility for the detection of metastases in mediastinal and hilar lymph nodes in lung cancer patients (22)(23)(24).…”
mentioning
confidence: 99%
“…They concluded that early-stage NSCLC located in the lower lobes was associated with upstaging after surgery. Another study investigating nodal upstaging was reported by AlSarraf et al (5). This is study evaluated the risk factors of inaccuracy in N staging (both downstaging and upstaging), and concluded that inaccurate nodal staging was common in patients with history of tuberculosis, rheumatoid arthritis, and diabetes mellitus.…”
Section: How Is Nodal Upstaging For Lung Cancer Defined?mentioning
confidence: 96%